Cigarette Smoke Exposure Increases Glucose-6-phosphate Dehydrogenase, Autophagy, Fibrosis, and Senescence in Kidney Cells In Vitro and In Vivo. (27th March 2022) - Liu, Wen-Chih; Chuang, Hsiao-Chi; Chou, Chu-Lin; Lee, Yu-Hsuan; Chiu, Yu-Jhe; Wang, Yung-Li; Chiu, Hui-Wen
Abstract : Cigarette smoke (CS) is a risk factor for chronic obstructive pulmonary disease. We attempted to investigate fully the possible effects of CS on kidney cells. We found that the viability of a human kidney proximal tubular epithelial cell line (HK-2 cells) was decreased after treatment with CS extract (CSE). In particular, the effects of CSE at low concentrations did not change the expression of apoptosis and necrosis. Furthermore, CSE increased autophagy- and fibrosis-related proteins in HK-2 cells. Senescence-related proteins and the senescence-associated secretory phenotype (SASP) increased after HK-2 cells were treated with CSE. In addition, both RNA sequencing and gene set enrichment analysis data revealed that glucose-6-phosphate dehydrogenase (G6PD) in the reactive oxygen species (ROS) pathway is responsible for the changes in CSE-treated HK-2 cells. CSE increased G6PD expression and its activity. Moreover, the inhibition of G6PD activity increased senescence in HK-2 cells. The inhibition of autophagy reinforced senescence in the CSE-treated cells. In a mouse model of CS exposure, CS caused kidney damage, including tubular injury and glomerulosclerosis. CS increased fibrosis, autophagy, and G6PD expression in kidney tissue sections. In conclusion, CS induced G6PD expression, autophagy, fibrosis, and senescence in kidney cells. G6PD has a protective role in CS-induced nephrotoxicity.